Social-demographic factors associated with Premenstrual Syndrome among female University students in Central Uganda: A Cross-sectional Study. - Elizabeth Atim; Florence Nabushawo Okecho; Regina Ndagire; Catherine Lwanira Nassozi (Student's Journal of Health Research, 2022)
Background Premenstrual Syndrome (PMS) is a common disorder among females of reproductive age, which also happens to be the most productive period within the life of a woman. Unfortunately, the aetiology of PMS is still not known; although, the following theories have been proposed to explain PMS symptoms: A genetic predisposition; changes in neurotransmitter levels; or changes in different hormone levels during the menstrual cycle.  In Uganda the factors associated with PMS are hardly documented, making awareness, prevention, and management complicated. The aim of this study, was to determine the social demographic factors associated with PMS among female university students in Central Uganda. Methodology A cross-sectional study was carried out using a self-administered questionnaire between November 2021 and May 2022. 238 female students in 4 universities who consented and met the inclusion criteria participated in the study. Data which was obtained about social demographic characteristics and PMS symptoms was coded and analysed to obtain descriptive statistics and Chi-square correlations.  Results The mean age of the respondents was 22.67±5.595, with most of the respondents (188, 88.7%) being between 19 to 24 years of age, the minimum age was 19 years and the maximum was 55 years. Among this study population, menarche age group χ2(2, n=212) = 7.756, p=0.021, and several menstrual bleeding days χ2(1, n=212) = 5.188, p=0.023 were associated with PMS among the female university students. Conclusion The cause of the PMS among this study population is likely biological as respondents who reported that they started their menses started at age ≤12 years; as well as those whose bleeding days were more than or equal to 5 days were more likely to suffer PMS. Recommendation Studies need to be carried out to investigate the biological causes of PMS to guide management and prevention.